Maths, German, and English teachers' student specific self-efficacy - is it a matter of students' characteristics? - Schwab, Susanne; Kulmhofer-Bommer, Andrea; Hoffmann, Lisa; Goldan, Janka (Educational psychology (Dorchester-on-Thames), 2021)
Over the last decades, teachers' self-efficacy beliefs have been widely investigated and defined as an overall construct. Recent studies indicate, however, that teachers' self-efficacy (TSE) beliefs vary depending on the individual student (so-called 'student-specific teacher self-efficacy', S-S TSE). Students' gender, their language background, their special educational needs (SEN) status or behaviour problems affect S-S TSE. This study analyses the S-S TSE of Maths, German and English teachers towards 507 secondary grade students from Germany. Results revealed that S-S TSE is higher on behaviour management than on instructional strategies, student engagement and emotional support. The overlap between the S-S TSE ratings of two teachers with different subjects towards the same student was rather moderate. Further findings show a high variance of S-S TSE on student-level which can be mainly explained by students' behavioural issues. Therefore, future research and practice should take individual students' characteristics into account when addressing TSE.